Legal Risk Analysis of Micro KUR Products Using Murabahah Bil Wakalah Contracts in Sharia KUR Financing: Analisis Risiko Hukum Produk Mikro KUR Yang Memakai Akad Murabahah Bil Wakalah Pada Pembiayaan KUR Syariah - Nisa, Fatika Khairun; Lestari, Nur Melinda (Universitas Muhammadiyah Sidoarjo, 2025)
KUR Sharia is one of the financing programs aimed at assisting micro, small, and medium enterprises in Indonesia. KUR Sharia is implemented by Islamic banks with the aim of increasing access to financing for micro, small, and medium enterprises that have not yet been reached by the conventional banking system. This financing product uses Sharia principles, which are expected to provide ease for entrepreneurs with lower interest rates and lighter requirements. This type of financing uses the murabahah bil wakalah contract, which is a sale and purchase system based on wakalah. In this sales system, the seller delegates the purchase to the customer, thus the first contract is the wakalah contract, and after the wakalah contract ends, it is followed by the Murabahah Bil Wakalah contract. This research uses a descriptive qualitative method that gathers information through interviews with employees of Bank Syariah Indonesia X. The results of this study indicate that legal risk arises due to the absence of supportive legislation or weaknesses in obligations, such as the failure to meet the valid contract requirements or the imperfect binding of collateral. This legal risk is closely related to financing risk. The impact on Islamic banks is the emergence of problematic financing, one of which is caused by weaknesses in collateral binding. As a result, Islamic banks face difficulties in executing collateral if financing risks occur. Thus, legal risk and financing risk must be identified, measured, monitored, and managed properly.